Immunogenic chemotherapy in two mouse colon cancer models. Issue 10 (1st September 2020) - Taniura, Takahito; Iida, Yuichi; Kotani, Hitoshi; Ishitobi, Kazunari; Tajima, Yoshitsugu; Harada, Mamoru
Abstract: Aside from the induction of cell death, some anticancer chemotherapeutic drugs can modulate antitumor immune responses. In this study, we examined the anticancer effects of 5‐fluorouracil (5‐FU) and oxaliplatin (L‐OHP), which are standard chemotherapeutic drugs for colon cancer, combined with cyclophosphamide (CP) in two mouse colon cancer models (CT26 and MC38 colon adenocarcinoma models). In the CT26 model, two injections of 5‐FU/L‐OHP and CP significantly suppressed the growth of subcutaneously established CT26 tumors compared with either 5‐FU/L‐OHP or CP, without a significant loss of body weight. The anticancer effect was weakened in nude mice. Cured mice acquired protective immunity against CT26, and CT26‐specific cytotoxic T cells (CTLs) were induced from their spleen cells. Analysis of tumor‐infiltrating immune cells revealed that 5‐FU/L‐OHP treatment with or without CP increased the proportion of CD8 + T cells at tumor sites. The 5‐FU/L‐OHP treatment decreased the proportion of granulocytic myeloid‐derived suppressor cells (MDSCs) and increased monocytic MDSCs in tumor sites, whereas the addition of CP treatment reversed these changes. In the MC38 model, although significant anticancer effects of the triple combination therapy were seen, additional treatment with anti‐PD‐1 antibody increased the number of cured mice. These mice exhibited protective immunity against MC38, and MC38‐specific CTLs were generated from their spleen cells. Together, these results indicate that the antitumor effects of the combination of 5‐FU/L‐OHP and CP mainly depend on host T cells; moreover, the therapeutic efficacy can be effectively boosted by immune checkpoint blockade. Abstract : Antitumor effects induced by the triple combination chemotherapy with 5‐FU/L‐OHP and cyclophosphamide.